Penguatan Kewirausahaan Untuk Mencetak Wirausahawan Muda pada Karang Taruna Kelurahan Kapuk Cengkareng Jakarta Barat - Suprapto, Hugo Aries; Widiyarto, Sigit; Setyowati, Luluk; Sandiar, Loecita; Nurisman, Husain (Jurnal Pengabdian UntukMu NegeRI, 2026)
The entrepreneurship training for 21 members of Karang Taruna in Kapuk Village, Cengkareng was held to address low youth readiness for entrepreneurship, limited access to marketing and technology, and the need to create local employment. The program aimed to cultivate an entrepreneurial mindset, identify local business opportunities, teach a simple business model (Business Model Canvas), utilize digital technology for marketing, introduce basic financial management, and explain legal aspects and the importance of networking. Activities were delivered through interactive presentations, group discussions, practical workshops on digital marketing, HPP (cost of goods sold) calculation simulations, and guidance on NIB registration. Results showed significant improvements in conceptual understanding and practical skills: participants were able to formulate business ideas based on local potential, create basic BMCs, produce promotional content for social media, access marketplaces, and separate business from personal finances while calculating HPP. Evaluations indicated knowledge scores averaging within a good range, reflecting initial readiness for business implementation with continued mentoring. In conclusion, the intervention effectively fostered proactivity, basic technical capacity, and member collaboration. Implications include the need for follow-up programs such as mentoring, facilitation of digital market access, and legal-administrative Keywords: Entrepreneurship, Young Entrepreneurs , karang taruna